Effect of feeding frequency on growth, proximate composition, and hemocyte status of Litopenaeus vannamei and Macrobrachium rosenbergii under nursery co-culture in a biofloc system - Halim, Md Abdul; Aziz, Dania; Arshad, Aziz; Wong, Nur Leena W. S.; Karim, Murni; Syukri, Fadhil; Rahi, Md Lifat (Oxford University Press, 2026)
Objective: We investigated the effect of feeding frequency (FF-2 [2 times/d], FF-3 [3 times/d], FF-4 [4 times/d], and FF-5 [5 times/d]) on nursery-based co-culture of Pacific white shrimp Litopenaeus vannamei and giant river prawns Macrobrachium rosenbergii in a biofloc system. Methods: The growth parameters, proximate composition, and hemocyte status of L. vannamei and M. rosenbergii were calculated. The physicochemical parameters, total bacterial load, and proximate composition of the biofloc were also measured among the treatments. Molasses was added (C:N ratio = 10:1), and salinity was 15‰. The experiment utilized twelve 125-L tanks, each containing 100 L of water. Each tank was stocked with 100 postlarvae, comprising 50 L. vannamei (mean±SD = 28.38±0.54 mg) and 50 M. rosenbergii (25.62±0.31 mg). Results: For L. vannamei, the specific growth rate (%/d) was significantly higher in FF-5 (mean±SD = 9.87±0.54) and lower in FF-2 (9.30±0.46). For M. rosenbergii, the specific growth rate was significantly higher in FF-3 (5.78±0.46) and lower in FF-2 (5.61±0.46). The survival rate for L. vannamei was significantly higher in FF-5 (mean±SD = 91.33±6.43%) and lower in FF-2 (86.00±13.86%). For M. rosenbergii, the survival rate was significantly higher in FF-5 (86.00±7.21%) and lower in FF-2 (72.00±10.58%). The feed conversion ratio was significantly better in FF-5 (1.29) for L. vannamei, whereas it was significantly better in FF-3 (2.08) for M. rosenbergii. Significantly higher hemocyte counts were recorded in FF-5 for both species. For L. vannamei and M. rosenbergii, significantly higher levels of crude protein, lipid, and ash were recorded in FF-5. The benefit–cost ratio was higher for FF-5 than for FF-4, FF-3, or FF-2. Conclusions: This study indicates that higher feeding frequencies improved the survival rate of L. vannamei and M. rosenbergii and enhanced their economic viability, productivity, and sustainability in aquaculture.